Phenome-wide Mendelian randomization study evaluating the association of circulating vitamin D with complex diseases - Xu, Jin-jian; Zhang, Xiao-bin; Tong, Wen-tao; Ying, Teng; Liu, Ke-qi (Frontiers in Nutrition, 2023)
Abstract Background: Circulating vitamin D has been associated with multiplewas linked to multifarious clinical diseases in observational studies, but the association was inconsistentfickle due to the presence of confounders. We undertook conducted a bidirectional mendelianMendelian randomization (MR) study to explore the healthy atlas of vitamin D in manynumerous diseases,clinical traits, and evaluate their causal association. Methods: Based on the large-scale genome-wide association study (GWAS), the single nucleotide polymorphisms (SNPs) instruments of circulating 25-hydroxyvitamin D (25OHD) levels from 443,734 Europeans and the corresponding effects of 10 clinical diseases and 42 clinical traits in European population were recruited to conduct bidirectional two-sample mendelianMendelian randomization studyies between serum 25-hydroxyvitamin D and multiple outcomes. Under the network of mendelianMendelian randomization analysis, inverse-variance weighting (IVW), weighted median, weighted mode, mendelianMendelian randomization (MR)-Egger regression were performed to explore the causal effects and pleiotropy. The mendelianMendelian randomization pleiotropy RESidual Sum and Outlier (MR-PRESSO) was conducted to uncover and exclude pleiotropic SNPs. Results: The results revealed that genetically decreased vitamin D was inversely correlated to decreased the estimated BMD (β= -0.029 g/cm2, p= 0.027), TC (β= -0.269 mmol/L, p= 0.006), TG (β= -0.208 mmol/L, p= 0.002), and pulse pressure (β= -0.241 mmHg, p= 0.043), while and positively associated with lymphocyte count (β= 0.037 %, p= 0.015). However, theThe results did not reveal any causal association of vitamin D with clinical diseases. Reversely, genetically protected CKD was significantly associated with increased vitamin D (β= 0.056, p= 2.361ⅹ10-26). Conclusions: The putative causal effects of circulating vitamin D on estimated bone mass, plasma triglyceride, and total cholesterol were observeduncovered, but not. on clinical Chronic kidney diseases will reduce circulating vitamin D levels. Vitamin D may be linked to clinical disease healthy outcomes by affecting health-related metabolic markers.